[Haskell-cafe] Re: Laziness question
stefan at vectorfabrics.com
Mon Aug 2 17:18:50 EDT 2010
>> h :: (x ~ y, Eval (y -> Int)) => (x -> Int) -> (y -> Int) -> Int
> But actually if you push the constraint inward, into the type so to say, you actually get quite close to Janis' and David's solution.
Sorry, I was thinking out loud there. I meant the Eval constraint, not the equality constraint. But, right now, I guess my comment only makes sense to me, so let's pretend I kept quiet. ;-)
More information about the Haskell-Cafe